Correlation of blood coagulation parameters with comorbidities in COVID-19 patients: A retrospective study - Shuba N; Michael A (Journal of Medical and Scientific Research)
COVID-19 is a respiratory pathogenic strain with the potential to cause severe systemic inflammation and coagulopathy. Moreover, dysfunctional coagulation cascades in diabetes mellitus and an imbalance of cytokines in hypertension and cardiovascular diseases may pose an additional risk towards hypercoagulability and subsequent mortality amid those with COVID-19. In this study, blood parameters that influence coagulation such as platelets, d-dimer and NLR ratios (neutrophil / lymphocyte ratio) were assessed between comorbid and non-comorbid individuals. Absolute neutrophil count, absolute lymphocyte count and hemoglobin levels were also assessed and tested for significance between the two groups. The NLR ratio was increased among those with comorbidities and showed a significant association between the two groups. Absolute neutrophil count was also significant and showed increased levels among those with comorbidities. These may indicate increased risks for coagulopathy amid individuals with comorbidities, although it is notable to mention that d-dimer levels were consistent, and platelets remained normal with insignificant variations between the two groups of individuals. Thus, further research is essential to conclude the possible risks for coagulopathy amid individuals with comorbidities.